Lean knowledge life cycle framework to support lean product development - Maksimovic, Maksim (Cranfield University, 2013)
This research thesis presents the development of a novel Lean Knowledge Life Cycle (LeanKLC) framework to support the transformation into a Lean Product Development (LeanPD) knowledge environment. The LeanKLC framework introduces a baseline model to understand the three dimensions of knowledge management in product development as well as its contextualisation with acclaimed LeanPD process models. The LeanKLC framework comprises 23 tasks, each accomplished in one of the seven key stages, these being: knowledge identification, previous knowledge capture, knowledge representation, knowledge sharing, knowledge integration, knowledge use and provision and dynamic knowledge capture. The rigorous research methodology employed to develop the LeanKLC framework entailed extensive data collection starting with a literature review to highlight the gap in the current body of knowledge. Additionally, industrial field research provides empirical evidence on the current industrial perspectives and challenges in managing product development knowledge. This research was part of a European FP7 project entitled Lean Product and Process Development (LeanPPD), which provided the opportunity to involve industrial collaborators in action research to support practical aspects during the LeanKLC framework development. The synthesis with the current LeanPD paradigm is accomplished by demonstrating the LeanKLC stages in two distinct streams related to the development of A3 thinking for problem solving and the development of trade-off curves to facilitate set based design at the conceptual stage. The novel LeanKLC is validated in two case studies providing the industry with detailed insights on real product development applications. In particular this research highlights that the LeanPD knowledge environment is a wide subject area that has not yet been thoroughly understood and that industry engagement in empirical research is vital in order to realise any form of LeanPD transformation.
Keywords: Three Dimensions of Knowledge Management; Lean Product Development; Knowledge Life Cycle; A3 Thinking; Trade-Off Curve